Pengaruh Strategi Berkompetisi dan Dukungan Komite Audit terhadap Pergerakan Laba serta Dampaknya terhadap Reaksi Pasar - Kiko Armenita Julito; Sihar Tambun; Eva Reviana (Jurnal Akuntansi Manajerial, 2023)
Companies that manage their resources optimally can be seen from the achievement of profits in accordance with predetermined targets. This shows that the company's financial performance is experiencing positive profit growth so that it is able to compete with other companies in the same business sector. The samples taken are companies active in the fields of e-commerce, information technology, and the consumer goods industry which are listed on the Indonesia Stock Exchange (IDX) with a time span of 4 years, namely from 2019-2022.  With the method of determining the sample using a purposive method. The sample used in this study was 30 companies with various considerations according to the criteria for sampling.  The results of this study using regression analysis accompanied by path analysis, especially testing the intervening variables which show that Competing Strategy has a significant negative effect on Profit Movements. Audit Committee Support has no significant and negative effect on Profit Movements. Profit movement has no significant effect on market reaction. Profit movement is unable to mediate the relationship between competitive strategy and market reaction. Profit movement is unable to mediate the relationship between Audit Committee Support to Market Reaction.